Converting Belief, Connecting People: The Kingdoms and the Dynamics of Islamization in Pre-Colonial Archipelago - Jajat Burhanudin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
The pre-colonial Archipelago period of Indonesian history witnessed rapid Islamization. The kingdoms or sultanates served as the centre of emerging Islamic socio-political and cultural dynamics. In this article, the crucial role that the kingdoms played in facilitating Islamization will be examined, giving strong emphasis to how they emerged as hubs for ‘ulamā’ who Islamized the people of the Archipelago. This process created an Islamic network with the ‘ulamā’ introducing rulers and society to Islam. Islamization unified the people in the “lands below the winds” under one religion. This connecting process was further facilitated by the rise of Malay language alongside the Jawi (Arabic) script as a medium for intra-regional communication as well as Islamic expression. The experience of being Islamized created a collective memory of being part of “the others” and laid a strong foundation for the unification of Indonesian society today.DOI: 10.15408/sdi.v25i2.5682